Novel Perspectives on the Development of the Amygdala in Rodents - Aerts, Tania; Seuntjens, Eve (Frontiers in Neuroanatomy, 2021)
The amygdala is a hyperspecialized brain region composed of strongly inter- and intraconnected nuclei involved in emotional learning and behavior. The cellular heterogeneity of the amygdalar nuclei has complicated straightforward conclusions on their developmental origin, and even resulted in contradictory data. Recently, the concentric ring theory of the pallium and the radial histogenetic model of the pallial amygdala have cleared up several uncertainties that plagued previous models of amygdalar development. Here, we provide an extensive overview on the developmental origin of the nuclei of the amygdaloid complex. Starting from older gene expression data, transplantation and lineage tracing studies, we systematically summarize and reinterpret previous findings in light of the novel perspectives on amygdalar development. In addition, migratory routes that these cells take on their way to the amygdala are explored, and known transcription factors and guidance cues that seemingly drive these cells towards the amygdala are emphasized. We propose some future directions for research on amygdalar development and highlight that a better understanding of its development could prove critical for the treatment of several neurodevelopmental and neuropsychiatric disorders.